Gain of 1q is associated with inferior event‐free and overall survival in patients with favorable histology Wilms tumor: A report from the Children's Oncology Group. Issue 21 (26th August 2013) - Gratias, Eric J.; Jennings, Lawrence J.; Anderson, James R.; Dome, Jeffrey S.; Grundy, Paul; Perlman, Elizabeth J.
Abstract : BACKGROUND: Wilms tumor is the most common childhood renal tumor. Although the majority of patients with favorable histology Wilms tumor (FHWT) have good outcomes, some patients still experience disease recurrence and death from disease. The goal of the current study was to determine whether tumor‐specific chromosome 1q gain is associated with event‐free survival (EFS) and overall survival (OS) in patients with FHWT. METHODS: Unilateral FHWT samples were obtained from patients enrolled on National Wilms Tumor Study‐4 and Pediatric Oncology Group Wilms Biology Study (POG 9046). 1q gain, 1p loss, and 16q loss were determined using multiplex ligation‐dependent probe amplification. RESULTS: The 8‐year EFS rate was 87% (95% confidence interval [95% CI], 82%‐91%) for the entire cohort of 212 patients. Tumors from 58 of 212 patients (27%) displayed 1q gain. A strong relationship between 1q gain and 1p/16q loss was observed. The 8‐year EFS rate was 76% (95% CI, 63%‐85%) for patients with 1q gain and 93% (95% CI, 87%‐96%) for those lacking 1q gain ( P  = .0024). The 8‐year OS rate was 89% (95% CI, 78%‐95%) for those with 1q gain and 98% (95% CI, 94%‐99%) for those lacking 1q gain ( P  = .0075). Gain of 1q was not found to correlate with disease stage ( P  = .16). After stratification for stage of disease, 1q gain was associated with a significantly increased risk of disease recurrence (risk ratio estimate: 2.72; P  = .0089). CONCLUSIONS: Gain of 1q may provide a valuable prognostic marker with which to stratify therapy for patients with FHWT. A confirmatory study is necessary before this biomarker is incorporated into the risk stratification schema of future therapeutic studies. Cancer 2013;119:3887–3894. © 2013 American Cancer Society. Abstract : Tumor‐specific gain of 1q is associated with inferior event‐free and overall survival in patients with favorable‐histology Wilms tumor and may provide a valuable prognostic marker with which to stratify therapy. A confirmatory study is necessary before this biomarker is incorporated into the risk stratification schema of future therapeutic studies.